1992
DOI: 10.1007/bf01759921
|View full text |Cite
|
Sign up to set email alerts
|

Structural optimization with crashworthiness constraints

Abstract: An automated structural design methodology has been devised which simultaneously considers design criteria associated with both linear elastic and crashworthiness loading conditions. This method is developed within the context of a nonlinear mathematical programming based structural optimization capability using an efficient two-phased crashworthiness analysis technique. Specially constructed nonlinear approximations for the crashworthiness constraints are employed to further reduce the computational burden du… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

1996
1996
2010
2010

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 9 publications
0
13
0
Order By: Relevance
“…In Chapter 3 it has been remarked that both single-point and multi-point approximations can be improved by inclusion of suitable intermediate design variables and responses. Lust ( 1992), for example, showed that for structural crash worthiness constraints, such as the vehicle crash severity index, intermediate design variables and responses can be defined that yield more robust constraint approximations. Probably many more can be found, reflecting the mathematical and physical background of the crashworthiness responses.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…In Chapter 3 it has been remarked that both single-point and multi-point approximations can be improved by inclusion of suitable intermediate design variables and responses. Lust ( 1992), for example, showed that for structural crash worthiness constraints, such as the vehicle crash severity index, intermediate design variables and responses can be defined that yield more robust constraint approximations. Probably many more can be found, reflecting the mathematical and physical background of the crashworthiness responses.…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Lumped parameters models have been proposed by Lust [6] and Kim et al [7] for crashworthiness structural optimization in the first stages of the design process. Mahmood et al [8] described in detail a procedure for rapid simulation and design of the frame of an automotive structure and Cheva et al [9] used lumped mass models for frontal/offset crash studies.…”
Section: Crashworthiness Simulation With the Mb Approachmentioning
confidence: 99%
“…It was also observed that the energy absorption capacity of the cylindrical tube was slightly better than that for the square tube for the same mass of the tubes. Lust (1992) considered optimization of automotive structures with constraints based on both linear elastic and crashworthiness loading conditions. A two phase crashworthiness analysis approach was used.…”
Section: Crashworthiness Analysismentioning
confidence: 99%